Pendampingan Pastoral Melawan Stigma Negatif pada Keluarga Orang dengan HIV/AIDS di Kota Ambon - Ruimassa, Aleta Apriliana; Tomasoa, Rineva Lenci (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
The societal stigma towards HIV/AIDS is not only directed at people living with HIV/AIDS (ODHA) but also towards their families. The stigma indirectly affects every aspect of family life and the relationships within it. This research aims to understand the impact of HIV/AIDS stigma on the families of PLWHA, and what the church has done regarding that stigma, then to design a pastoral theology that culminates in pastoral accompaniment actions for the families of PLWHA. In this study, the author uses Richard Osmer's practical theology method. The research results show that the stigma directed at families of PLWHA affects their lives and the relationships between each family member, which indirectly impacts the roles and functions of PLWHA families. Additionally, it is known that there has not yet been any pastoral care specifically aimed at PLWHA families. Pastoral care for PLWHA families should be based on the values of solidarity and brotherhood to fight alongside PLWHA families. The church must become an inclusive church to continue supporting PLWHA and their families.